Pengaruh Visi Dan Misi Terhadap Gaya Mengajar Dosen Dan Motivasi Belajar Mahasiswa Di Politeknik LP3I Jakarta - Jaenudin Akhmad; Sulaeman, Iman; Nur Haris Ependi (ASIAN PUBLISHER, 2022)
This research was conducted with the aim of knowing the influence of the vision and mission of educational institutions on the teaching style of lecturers and students' learning motivation at the LP3I Jakarta Polytechnic which is expected to be input or information and evaluation for the Jakarta LP3I Polytechnic to be taken into consideration and improvement in accordance with the policies and provisions stipulated apply and become material for discourse and study in an effort to broaden insight into issues related to the vision and mission of institutions and study programs, teaching styles of lecturers and student motivation. This study uses quantitative methods. The population in this study were all lecturers and students at the LP3I Jakarta Polytechnic in the 2015/206 academic year and the sampling in this study was carried out by purposive sampling method. Purposive sampling is a technique that mixes subjects in the population so that all subjects are considered equal, thus, the researcher gives equal rights to each subject to have the opportunity to be selected as a sample with certain criteria/objectives. Data collection was done through observation, interviews using a questionnaire with a data analysis tool, namely SPSS version 17.00